FILOSOFÍA DE LAS MATEM ÁTICAS,TEORÍA DE CARDINALES GRANDES Y SUS BASES COGNITIVAS. - Quezada, Wilfredo (Revista de Filosofía (00348236), 2017)
In this paper we examine in first place some philosophical implications of P. Maddy's mathematical naturalism as a philosophical account which allows us to overcome the drawbacks associated to both fictionalism and physicalistic realism in philosophy of mathematics. Besides that, the main virtue of that account seems to lie in the solution it provides to the applicability of mathematics problem when rejecting both the indispensability thesis and confirmative holism postulated by Quine. In second place, on the basis of difficulties intrinsic to Maddy's philosophical program, we explore a better motivated naturalistic option -the embodied cognition approach- and suggest that it allows to adequately explain why most of set-theory specialists use to postulate the existence of some large cardinals, in particular, non-constructible sets.